Situational Awareness and Patient Safety Culture: The Mediating Role of Effort–Reward Imbalance in Hospitals - Septa Reni; Tjipto Rini; Sandra Dewi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Patient safety culture is an essential component in improving the quality of healthcare services and preventing medical errors in hospitals. However, the implementation of patient safety culture is often influenced by several organizational and individual factors, including situational awareness, availability of hospital infrastructure, and the balance between effort and rewards experienced by healthcare workers. This study aims to analyze the influence of situational awareness and hospital infrastructure on patient safety culture, with effort–reward imbalance acting as a mediating variable. The research was conducted at RSIA Tiara and involved healthcare workers as respondents. A quantitative approach with a cross-sectional design was applied in this study. Data were collected through structured questionnaires distributed to healthcare professionals and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that situational awareness has a significant positive effect on effort–reward imbalance and patient safety culture. Hospital infrastructure also significantly influences effort–reward imbalance and patient safety culture. Furthermore, effort–reward imbalance significantly affects patient safety culture and mediates the relationship between situational awareness, hospital infrastructure, and patient safety culture. These findings indicate that improving healthcare workers’ situational awareness and ensuring adequate hospital infrastructure can help reduce work imbalance and strengthen patient safety culture. In conclusion, hospital management should prioritize training programs to enhance situational awareness, improve supporting facilities, and implement fair reward systems to promote a sustainable and positive patient safety culture in healthcare organizations.